Fundamental British and "The Other" Values—An Analytical Reflection on Implications for Home Education. Issue 1 (May 2020) - Pattison, Harriet
This paper reflects on the question of whether, and how, Fundamental British Values (FBVs) may affect the practice of home education in the UK. Fundamental British Values were introduced into the national curriculum in 2014, for state administered schools and preschools which have since been required to demonstrate that FBVs are embedded in the practice of the setting. Home educators, on the other hand, are not obliged to follow the national curriculum meaning that the effect of FBVs on such alternative education is not obvious. However, this paper draws attention to the wider environment of home education by considering FBVs as the product of three particular spheres of contemporary discourse as they interrelate and influence each other. These are the affordances of identity in a postinternational era, expressions of Foucauldian governmentality in terms of self-surveillance and management, and the developmental paradigm. Fundamental British Values, alongside the concept of parenting and the materialization of a particular social morality, are considered as the inescapably emergent products of the un/reason created by the overlapping of these discourses. Their convergence, in turn, creates a weight of logic from which FBVs exert influence over the practice and judgment of alternative forms of education.